Efficacy of short period, low dose oral prednisolone for the prevention of stricture after circumferential endoscopic submucosal dissection (ESD) for esophageal cancer - Kataoka, Mikinori; Anzai, Sho; Shirasaki, Tomoaki; Ikemiyagi, Hidekazu; Fujii, Takashi; Mabuchi, Kazuhisa; Suzuki, Shinji; Yoshida, Masashi; Kawai, Takashi; Kitajima, Masaki (Endoscopy International Open, 2015)
Background and aims: Endoscopic submucosal dissection (ESD) was developed in Japan and has been performed on many patients with early stage esophageal cancer; however quality of life in patients with postoperative stricture is drastically decreased and repeat, periodic endoscopic balloon dilatation (EBD) is usually required over long periods. In this study, we evaluate the efficacy of short period, low dose oral prednisolone in controlling post-procedural esophageal stricture. Patients and methods: In total, 33 patients who underwent semicircular or complete circular ESD for esophageal superficial squamous cell carcinoma were included in this study. They were divided into two groups: those who underwent large-circumference ESD with no preventative treatment for stricture (ESD alone group) and those who received systemic steroid treatment for stricture (oral prednisolone group). We compared the two groups in terms of stricture rate and total number of EBD sessions. The ESD alone group underwent no preventative treatment. The oral prednisolone group started with 30 mg/day prednisolone on the second day post-ESD, and continued with a gradually tapering prednisolone dose, finally discontinuing systemic steroid administration 3 weeks later. Results: The stricture rate after ESD was significantly lower in the oral prednisolone group (3 of 17 patients; 17.6 %) than in the ESD alone group (11 of 16 patients; 68.7 %) (P < 0.01). The number of EBD sessions was significantly lower in the oral prednisolone group than in the ESD alone group (median 4.6, range 2 – 10 vs. median 8.1, range 1 – 18; P < 0.01).Conclusion: Short period, low dose oral prednisolone showed promising results for the prevention of stricture after ESD for early stage esophageal cancers.